La irrupción de Hispania en los movimientos socioeconómicos del Mediterráneo Occidental durante las Guerras Civiles - Molina Vidal, Jaime (Gerión. Revista de Historia Antigua, 2002)
The present study analyses the changes experienced by the Hispanic economy at the end of the Republican era, enabling production to exceed modest levels and to penetrate into the Mediterranean markets, including Rome itself. We have maintained that the inrush of Hispanic goods must have taken place before the August era, during the Civil War period. We have also provided new elements that focus on this period, and especially that the Caesar, as being a key moment in the Hispanic economy that was to become a main focus in migratory movements, investments and new techniques, as well as approaches in agricultural and commercial production. Likewise, we have pointed out some of the repercussions that this peak in the Hispanic economy had, for example, in the investments that took place in the Italian peninsula, or the decadence of Apulian agriculture.